Efeito da microgravidade simulada em fibroblastos de pele humana - Bellicanta, Patrícia Lazzarotto (2016)
Introduction: The inherent characteristics of plasticity of human fibroblast cells makes it an important tool for evaluating the effects of microgravity at a cellular level. This study analyzed the behavior of human skin fragment fibroblasts in a simulated microgravity environment. Methods: Human fibroblast cells in the 8th and 17th passage, cultured under standard incubator conditions at 37° C with 5% CO2, were submitted to simulated microgravity in a 3D-clinostat for a period of 24h and 40h. After exposure, both passage cells were analyzed and compared with the control group (1G) in population doubling assays, tests of passage and microscopic analysis, as well as PCR analysis for detection of variations in the gene expression related to the cell cycle (p21, p16). Results: Before microgravity exposure, cells belonging to the 17th passage presented characteristics of cells in an apoptotic state. After 24h and 40h of microgravity, the cells of both groups showed themselves to be more confluent and elongated. PCR analysis demonstrated that p21 expression was decreased while p16 increased. In addition, PCR analysis showed a difference in expression of p21 and p16 genes between the 24h and 40h samples. Discussion: The present research showed cells to be more confluent and elongated after microgravity exposure, a characteristic of cells with fewer passages, suggesting alterations in their cytoskeleton. This result was confirmed by PCR analysis where a decrease in p21 expression was demonstrated. This result corroborates previous findings that among 588 genes tested, the p21 gene presented a negative expression. Conversely, the p16 gene showed a positive expression. Since both the p21 and p16 genes are related to the cell cycle, these results suggest the hypothesis of important changes having occurred in the cellular cytoskeleton and, consequently, a probable alteration in the production of cell cycle regulatory proteins (cyclins). Furthermore, RT-PCR analysis demonstrated a difference in p21 and p16 gene expression between the 24h and 40h samples, indicating the need for a more detailed comparison between the exposure times. Also pluripotency markers were found, Oct4 and Nanog, which suggests alterations in plasticity levels.